Neuropathy Target Esterase Gene Mutations Cause Motor Neuron Disease - Rainier, Shirley; Bui, Melanie; Mark, Erin; Thomas, Donald; Tokarz, Debra; Ming, Lei; Delaney, Colin; Richardson, Rudy J.; Albers, James W.; Matsunami, Nori; Stevens, Jeff; Coon, Hilary; et al. (American journal of human genetics, 2008)
The possibility that organophosphorus (OP) compounds contribute to motor neuron disease (MND) is supported by association of paraoxonase 1 polymorphisms with amyotrophic lateral sclerosis (ALS) and the occurrence of MND in OP compound-induced delayed neuropathy (OPIDN), in which neuropathy target esterase (NTE) is inhibited by organophosphorylation. We evaluated a consanguineous kindred and a genetically unrelated nonconsanguineous kindred in which affected subjects exhibited progressive spastic paraplegia and distal muscle wasting. Affected subjects resembled those with OPIDN and those with Troyer Syndrome due to SPG20/spartin gene mutation (excluded by genetic linkage and SPG20/spartin sequence analysis). Genome-wide analysis suggested linkage to a 22 cM homozygous locus (D19S565 to D19S884, maximum multipoint LOD score 3.28) on chromosome 19p13 to which NTE had been mapped (GenBank AJ004832). NTE was a candidate because of its role in OPIDN and the similarity of our patients to those with OPIDN. Affected subjects in the consanguineous kindred were homozygous for disease-specific NTE mutation c.3034A→G that disrupted an interspecies conserved residue (M1012V) in NTE's catalytic domain. Affected subjects in the nonconsanguineous family were compound heterozygotes: one allele had c.2669G→A mutation, which disrupts an interspecies conserved residue in NTE's catalytic domain (R890H), and the other allele had an insertion (c.2946_2947insCAGC) causing frameshift and protein truncation (p.S982fs1019). Disease-specific, nonconserved NTE mutations in unrelated MND patients indicates NTE's importance in maintaining axonal integrity, raises the possibility that NTE pathway disturbances contribute to other MNDs including ALS, and supports the role of NTE abnormalities in axonopathy produced by neuropathic OP compounds.